La parole déchue dans « The House » de Sharunas Bartas - Louis Daubresse (Mise au Point, 2013)
Sharunas Bartas is a filmmaker whose work is characterized by an almost complete disappearance of speech. In his film « The House », he stages frantic and mute characters. The aesthetic choice he makes by resorting to silence encourages the spectators to question the relation between man and language. Silence imposes itself as a form of resistance to verbal abuse. It also releases some unsuspected ways of communication between the characters…